A decomposition analysis of regional poverty in Russia - Stanislav Kolenikov; Anthony Shorrocks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper applies a new decomposition technique to the study of variations in poverty across the regions of Russia. The procedure, which is based on the Shapley value in cooperative game theory, allows the deviation in regional poverty levels from the all- Russia average to be attributed to three proximate sources; mean income per capita, inequality, and local prices. Contrary to expectation, regional poverty variations turn out to be due more to differences in inequality across regions than to differences in real income per capita. However, when real income per capita is split into nominal income and price components, differences in nominal incomes emerge as more important than either inequality or price effects for the majority of regions.
Keywords: C15; C43; D31; P36; R12; 330; poverty; Russia; regions; decomposition; Armut; Räumliche Verteilung; Russland